If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-19=-3t+2
We move all terms to the left:
-19-(-3t+2)=0
We get rid of parentheses
3t-2-19=0
We add all the numbers together, and all the variables
3t-21=0
We move all terms containing t to the left, all other terms to the right
3t=21
t=21/3
t=7
| 3(n+1)(3n−1)=0 | | 1=g4− 2 | | 3=13e-19 | | ½y+5=y-3 | | x³-6x-1=0 | | 29-17*n=158 | | 18k−8k=20 | | –4x+6=34 | | −5(−3x−4)= | | 15=8-4y | | 1x-35=14 | | 1.25(4x-10)=7.5` | | 5(x-1)=5/4x | | V/n=4 | | n18=17 | | `1.25(4x-10)=7.5` | | 3(u+4)=-2(5u-2)+7u | | 3x+5.7=9 | | `2x+7=12` | | (12-9x)=3 | | a/7+21=9 | | 3y-9+2(4y+6)=-5(y+3) | | 5=4 3x+7 3 | | 391=p+233 | | a7+21=9 | | 12x+3=2x+12 | | -6(-4y+8)-4y=6(y-6)-2 | | 4x–6=2x+14 | | 4x+65x+1=x | | 16+x/7=11 | | 12y-5y+5-2=24 | | -4(-7x+7)-7x=5(x-1)-5 |